Excited-state spin-resonance spectroscopy of VB− defect centers in hexagonal boron nitride - Mathur, Nikhil; Mukherjee, Arunabh; Gao, Xingyu; Luo, Jialun; McCullian, Brendan A.; Li, Tongcang; Vamivakas, A. Nick; Fuchs, Gregory D. (Nature communications, 2022)
The recently discovered spin-active boron vacancy (V B − ) defect center in hexagonal boron nitride (hBN) has high contrast optically-detected magnetic resonance (ODMR) at room-temperature, with a spin-triplet ground-state that shows promise as a quantum sensor. Here we report temperature-dependent ODMR spectroscopy to probe spin within the orbital excited-state. Our experiments determine the excited-state spin Hamiltonian, including a room-temperature zero-field splitting of 2.1 GHz and a g-factor similar to that of the ground-state. We confirm that the resonance is associated with spin rotation in the excited-state using pulsed ODMR measurements, and we observe Zeeman-mediated level anti-crossings in both the orbital ground- and excited-state. Our observation of a single set of excited-state spin-triplet resonance from 10 to 300 K is suggestive of symmetry-lowering of the defect system from D 3 h to C 2 v . Additionally, the excited-state ODMR has strong temperature dependence of both contrast and transverse anisotropy splitting, enabling promising avenues for quantum sensing. The negatively charged boron vacancy in hBN shows promise as a quantum sensor, but, until recently, the focus has been on its ground-state properties. Here, the authors report temperature-dependent spin-resonance optical spectroscopy of the orbital excited state.